A Conceptual Framework for Integrating Gamification in eLearning Systems Based on Instructional Design Model - Yamani, Hanaa Abdulraheem (International journal of emerging technologies in learning, 2021)
The current paper aims to introduce a proposed framework for gamification in the e-learning system at Saudi Arabia universities, by reviewing and analyzing the concept of gamification and its components, and types of players, as well as conditions for designing successful gamification, and the technical capabilities of Saudi Arabia universities, and also by reviewing and analyzing many designing models for gamification and e-learning systems that were introduced by the other researchers. Then incorporate all of these previous considerations into the general stages of instructional design, which is represented in analysis, design, development, implementation, and evaluation. The paper also deals with a review of the difference between gamification, games, and game-based learning, in addition to the benefits for students from employing gamification in the e-learning system.